Combined treatment with vacuum sealing drainage, TopClosure device, and Ilizarov technique for traumatic hemipelvectomy: A rare case report of successful repairing of large-size soft tissue defects. Issue 4 (January 2019) - Li, Jin; Shi, Jie Bao; Hong, Pan; Wang, Yu Shang; Ze, Hao Ren; Lee, Rushyuan Jay; Tang, Xin
Abstract: Rationale: Traumatic hemipelvectomy is a rare but lethal catastrophic injury. Patient concerns: A case of a very young child with open fracture of left sacroiliac joint dislocation and pubic symphysis diastasis, suffered from a severe large-size soft tissue defects. Diagnosis: Traumatic hemipelvectomy. Interventions: Complete amputation was performed and three kinds of surgical techniques including regulated negative pressure-assisted wound therapy (RNPT), TopClosure device, and Ilizarov technique were jointly utilized to secure closure in the further revisions of the soft tissue injury and reconstruct reconstructive surgery. Outcomes: Six months after hospital discharge, the patient was able to ambulate with a single limb and a prosthesis and she is independent in many activities of daily living currently. Lessons: We report this case to share experience with other clinicians in the management of this deadly extensive defects after traumatic hemipelvectomy in patients.